The Perfect Pair: Bloch, Febvre, and the History of Science and Technology - Diogo Maria Paula (HoST, 2020)
Launched in 1929 by Marc Bloch and Lucien Febvre, the Annales gave rise to a groundbreaking approach to history known as the École des Annales. Based on the study of social history over a long-term period or longue durée, the new paradigm emphasized the collective nature of the mentalités and the importance of a multilayered analysis of society. The Annales reclaim the history of science and the history of technology as part of history as a whole and inextricably linked to the intellectual context of a specific time period. In this article, based on the Annales and UNESCO’s History of Mankind, I will focus on Bloch’s and Febvre’s stands on history and their relevance to the history of science and technology, particularly by championing the relevance of material and mental tools to understand each historical moment and by critically exploring the concepts of mentalités, histoire-problème, histoire totale and historical temporality.